The frequency of detection of the active form of helicobacter pylori infection in patients with chronic non-atrophic gastritis with biliary dyskinesia on the hypotonic hypokinetic type and with preserved function of the gall bladder - Korolenko, R. N.; Avramenko, A. A. (Journal of Education, Health and Sport, 2019)
The frequency of detection and the degree of dissemination of the gastric mucosa by the active form of Helicobacter pylori in 70 patients with chronic non-atrophic gastritis with biliary tract dyskinesia (BTD) by hypotonic hypokinetic type and in 70 patients with chronic non-atrophic gastritis with preserved function of the bladder were analyzed. In the group of patients with BTD according to the hypotonic hypokinetic type, the frequency of occurrence of the active form of Helicobacter pylori infection in different topographic zones of the stomach ranged from 24.3% to 35.7% with a moderate degree of mucous contamination - (+), while in the group of patients with preserved the function of the gallbladder, the frequency of occurrence of the active form of Helicobacter pylori infection in different topographic zones of the stomach ranged from 61.4% to 71.1% with a moderate degree of dissemination of the mucous membrane (++).